Chapter 2 Is journalism gender e-qual? - De Vuyst, Sara (Taylor & Francis, 2020)
Chapter 2 explores the gender aspects of digital skills in journalism. There is a discussion of the gendered consequences of the increased value of digital skills in journalism. For example, what happens if media companies hire more people with a background in ICT, a field which is notorious for its gender imbalance both in education and professions? In order to gain a complete picture of gender dimensions, the book not only focuses on quantitative aspects but also asks more complex questions about how gender interacts with technology in journalism. The answers to these questions goes beyond merely describing gender divides, by offering insights into the underlying mechanisms that support them. Obstacles that are addressed here include the geek stereotype, the gendered evaluation of digital skills, the coding ceiling, and the gendered accumulation of digital skills. The chapter focuses on how female and male journalists experience and perceive these obstacles in their professional lives based on qualitative interviews with an international sample of journalism professionals (n = 37).